Effectiveness of emotionally coupled therapy and redecision therapy on changing of marital communication skills in married women - Seyed Jamal Raisi; Korosh Mohammadi; Eghbal Zarei; Samaneh Najarpouriyan (مجله دانشگاه علوم پزشکی گرگان, 2018)
Background and Objective: Considering the communication patterns of couples is one way of looking at the structure of the family through which spouses interact each other. This study was carried out to determine the effectiveness of emotionally coupled therapy and redecision therapy on changing of marital communication skills in married women. Methods: This quezi-expermental study was done on 30 women who were chosen via available sampling through distressed women referred to centers of counselling in Gorgan, northern Iran during 2016. Selected women non-randomly divided in three groups including control, treated with emotionally focused couple therapy intervention and the redecision therapy intervention groups. Women in control group did not receive any intervention. Communication styles questioner was used for pretest and post test. Results: Emotionally focused couple therapy and redecision therapy significantly improved the communication styles of married women and maintain healthy gains, even up to six months after treatment (P<0.05). There was no significant difference between the effectiveness of emotionally focused couple therapy and redecision therapy methods. Conclusion: Emotionally focused couple therapy and redecision therapy have the same effect on improvement of communication styles of married women.